(untitled) (Colombia Medica, 2024)
Case Description A 23-year-old male patient, with no relevant medical history, who received direct contusion to the lower limbs at the level of the thighs due to a fall from a sheet bending machine. Clinical Findings Clinical and radiographic findings compatible with bilateral comminuted sub-trochanteric fractures, with extension towards the diaphysis in both, with a Trauma Severity Index of 16. Treatment and Outcome Favorable clinical and radiological outcome after early definitive surgical stabilization of both extremities with cephalomedullary nails, rehabilitation with physical therapy and clinical follow-up. Clinical Relevance High energy trauma, due to different causes, constitutes a challenge for all health personnel, due to the patient’s own conditions, the individual inflammatory response, the associated musculoskeletal injuries, some not detected at the beginning, and additionally in other systems. Patients with bilateral femur fractures may present the conditions listed above, which requires early identification of the risks of respiratory and multi-organ failure, knowledge of their metabolic status and definition of their clinical situation, considered potentially or truly critical, which even with timely treatment Mortality figures of 6.9% to 27% are found. According to defined parameters, early and definitive osteosynthesis of fractures can be performed, but its characteristics may represent difficulties for surgical planning.